Interconnection of Mathematics and Dhuha Time - Irsal, Irni Latifa; Monika, Monika (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The interconnection of mathematics and religion can be done by looking at the interconnectedness of mathematics and the sunnah dhuha. The uniqueness of the sunnah dhuha, provides a challenge to see how mathematics is present in the initial determination of the dhuha time, to make it easier for humans to do. In this study, the library research method was used as a research method to see the mathematical interconnection with dhuha time. There are four steps carried out in the research, the first is data collection, the second is data reduction, third is display data, and fourt data analysis and interpretation. From the research that has been done, the mathematical concepts that exist in determining the timing of the dhuha prayer are the basic concepts of mathematical arithmetic operations (addition, subtraction, multiplication, and division), trigonometric concepts, basic concepts of geometry (acute angles), and the concept of calculating time. . In the initial calculation of the implementation of dhuha prayer, the concept of trigonometry (sin, cos, tan), the basic concepts of arithmetic operations, and the concept of calculating the amount of time used. The basic concept of geometry (an acute angle) is connected with the angle formed at the height of the sun at the beginning of the time of the dhuha prayer seen from the observer.